2012
DOI: 10.1097/inf.0b013e318253add3
|View full text |Cite
|
Sign up to set email alerts
|

Postmarketing Surveillance of Intussusception Following Mass Introduction of the Attenuated Human Rotavirus Vaccine in Mexico

Abstract: This is the largest surveillance study for intussusception after rotavirus vaccination to date. A temporal increase in the risk for intussusception was seen within 7 days of administration of the first vaccine dose. It is still uncertain whether rotavirus vaccination has any impact on the overall incidence of intussusception. This finding has to be put in perspective with the well-documented substantial benefits of rotavirus vaccination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
69
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 30 publications
7
69
1
2
Order By: Relevance
“…Title and abstract screening resulted in the identification of 16 potentially relevant publications. Ten of these 16 studies met the inclusion criteria for the meta-analysis (Table 1) (18,(26)(27)(28)(29)(30)(31)(32)(33)(34). The publications not included in the full text screening are listed as references e2-e7.…”
Section: Resultsmentioning
confidence: 99%
“…Title and abstract screening resulted in the identification of 16 potentially relevant publications. Ten of these 16 studies met the inclusion criteria for the meta-analysis (Table 1) (18,(26)(27)(28)(29)(30)(31)(32)(33)(34). The publications not included in the full text screening are listed as references e2-e7.…”
Section: Resultsmentioning
confidence: 99%
“…One study estimated Rotarix increased risk by 3.7 additional cases per 100 000 person years in Mexico. 87 The other Latin American study estimated risk as 1 case per 51 000 vaccinations in Mexico and 1 case per 68 000 vaccinations in Brazil. 88 In sum, there is moderate strength evidence that vaccination against rotavirus is associated with intussusception, but the occurrence is extremely rare, and risk factors have not been investigated.…”
Section: Rotavirus Vaccines: Rotateq and Rotarixmentioning
confidence: 99%
“…We identified 5 postlicensure studies on intussusception risk [86][87][88][89][90] ; an earlier brand of rotavirus vaccine (Rotashield) was withdrawn from the market in 1999 due to concerns about risk for this condition. A high-quality epidemiologic study (N = 296 023) conducted in Australia 86 found RotaTeq associated with intussusception in children 1 to 21 days after the first of 3 required doses but found no association with Rotarix.…”
Section: Rotavirus Vaccines: Rotateq and Rotarixmentioning
confidence: 99%
“…In a recent Mexican PMS study, a temporal increase in the risk of IS within 7 d of receiving the first dose of Rotarix™ was observed. 17 This translated to an estimated 3.7 (95.5% CI: 1.2-7.3) cases of IS per 100 000 person-years which could be attributed to Rotarix™ vaccination. 17 These observations were also consistent with another study conducted in Australia, where the relative risk of IS in infants during the first 7 d after the first dose of Rotarix™ was 3.41 (95% CI: 0.70-9.96).…”
Section: Discussionmentioning
confidence: 99%
“…17 This translated to an estimated 3.7 (95.5% CI: 1.2-7.3) cases of IS per 100 000 person-years which could be attributed to Rotarix™ vaccination. 17 These observations were also consistent with another study conducted in Australia, where the relative risk of IS in infants during the first 7 d after the first dose of Rotarix™ was 3.41 (95% CI: 0.70-9.96). 18 Another case-control study in Mexican and Brazilian infants reported an increased risk of intussusception during the first 7 d after receiving the first dose in Mexico (odds ratio = 5.8 [95% CI: 2.6-13.0]) and during the first 7 d after receiving the second dose in Brazil (odds ratio = 1.9 [95% CI: 1.1-3.4]).…”
Section: Discussionmentioning
confidence: 99%